Gut Clostridium sporogenes-derived indole propionic acid suppresses osteoclast formation by activating pregnane X receptor - Renpeng Peng; Chao Song; Shuangquan Gou; Haiyang Liu; Honglei Kang; Yimin Dong; Yong Xu; Peixuan Hu; Kaiyong Cai; Qian Feng; Hanfeng Guan; Feng Li (Elsevier, 2024)
Bone homeostasis is maintained by osteoclast-mediated bone resorption and osteoblast-mediated bone formation. A dramatic decrease in estrogen levels in postmenopausal women leads to osteoclast overactivation, impaired bone homeostasis, and subsequent bone loss. Changes in the gut microbiome affect bone mineral density. However, the role of the gut microbiome in estrogen deficiency-induced bone loss and its underlying mechanism remain unknown. In this study, we found that the abundance of Clostridium sporogenes (C. spor.) and its derived metabolite, indole propionic acid (IPA), were decreased in ovariectomized (OVX) mice. In vitro assays suggested that IPA suppressed osteoclast differentiation and function. At the molecular level, IPA suppressed receptor activator of nuclear factor kappa-Β ligand (RANKL)-induced pregnane X receptor (PXR) ubiquitination and degradation, leading to increased binding of remaining PXR with P65. In vivo daily IPA administration or repeated C. spor. colonization protected against OVX-induced bone loss. To protect live bacteria from the harsh gastric environment and delay the emptying of orally administered C. spor. from the intestine, a C. spor.-encapsulated silk fibroin (SF) hydrogel system was developed, which achieved bone protection in OVX mice comparable to that achieved with repeated germ transplantation or daily IPA administration. Overall, we found that gut C. spor.-derived IPA was involved in estrogen deficiency-induced osteoclast overactivation by regulating the PXR/P65 complex. The C. spor.-encapsulated SF hydrogel system is a promising tool for combating postmenopausal osteoporosis without the disadvantages of repeated germ transplantation.